Physiological and ecological responses of flue-cured tobacco to field chilling stress: insights from metabolomics and proteomics - Gu, Kaiyuan; Li, Xinkai; Su, Jiaen; Chen, Yi; Yang, Chengwei; Li, Juan; He, Chenggang; Hu, Binbin; Zou, Congming (Frontiers in Plant Science, 2024)
Currently, research on tobacco's response to chilling stress is mostly limited to laboratory simulations, where temperature is controlled to study physiological and molecular responses. However, laboratory conditions cannot fully replicate the complex environment of field chilling stress, so conducting research under field conditions is crucial for understanding the multi-level adaptive mechanisms of tobacco to chilling stress in natural environments. This study aims to use field trials, starting from physiological responses, combined with proteomics and untargeted metabolomics, to systematically reveal the physiological and biochemical characteristics and key molecular mechanisms of tobacco leaves under chilling stress.It provides new insights into tobacco's adaptation strategies under chilling stress. The results showed that (1) chilling stress damages the appearance of tobacco leaves, reduces the chlorophyll content, increases H2O2 and MDA levels in cold-injured tobacco leaves, and damages the plasma membrane system. Although CAT activity increases to cope with the accumulation of ROS, the activities of key antioxidant enzymes SOD and POD significantly decrease, indicating that the antioxidant system of tobacco leaves fails in environments with sudden temperature drops. (2) Proteomics analysis indicated that 410 differentially expressed proteins were identified in cold-stressed tobacco leaves, with 176 upregulated and 234 downregulated. Tobacco leaves under chilling stress attempt to maintain energy supply and physiological stability by enhancing glycolysis, starch, and sucrose metabolism pathways. Concurrently, chilling stress triggers the expression of proteins related to cell wall reinforcement and antioxidant defense. However, due to impaired ribosomal function, protein synthesis is significantly inhibited, which aggravates damage to photosynthesis and cellular functions.(3) Metabolomics analysis revealed that the differential metabolites in cold-stressed tobacco leaves were mainly enriched in tyrosine metabolism, isoquinoline alkaloid biosynthesis, and fatty acid degradation pathways. This indicates that under chilling stress, tobacco leaves enhance adaptability by regulating energy metabolism, increasing antioxidant capacity, and stabilizing cell membrane structure. Therefore, under chilling stress, tobacco leaves exhibit complex physiological adaptability through multiple regulatory mechanisms involving proteins and metabolites. The research results provide important insights into the metabolic regulatory mechanisms of tobacco in response to extreme environments and also enhance the theoretical foundation for addressing low-temperature stress in practical production.